If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 6c + -12 Reorder the terms: 2 = -12 + 6c Solving 2 = -12 + 6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6c' to each side of the equation. 2 + -6c = -12 + 6c + -6c Combine like terms: 6c + -6c = 0 2 + -6c = -12 + 0 2 + -6c = -12 Add '-2' to each side of the equation. 2 + -2 + -6c = -12 + -2 Combine like terms: 2 + -2 = 0 0 + -6c = -12 + -2 -6c = -12 + -2 Combine like terms: -12 + -2 = -14 -6c = -14 Divide each side by '-6'. c = 2.333333333 Simplifying c = 2.333333333
| 10d=25 | | 4x-6x+2x= | | 5x-15+4x+-12=3x-1 | | 8x+-10=2x-14 | | 4z-2=-10 | | -3x-16x= | | 4(-5)-2=-10 | | 3(x+1)-x=x+1 | | 4z(-5)=-10 | | 27+6t-t^2=0 | | h+1.5=8.5 | | a+(a-1)+2a=47 | | 2x^2+15x+13=0 | | 3x+6+4x-5=10 | | (x+1)(x-3)=(x+2)(x+1) | | 7x+14=6x+30 | | d+48= | | d+48=5 | | 5x+5=4x+32 | | 6y=144 | | a+1=0 | | 17G-10=14G+20 | | 12M-10=10M+10 | | t=2m+2v | | 7P-2=3P+2 | | 2(3r+4)-3(r+1)=11 | | 10M+45=15M | | x^2=42 | | 5y-3y=15 | | (7x-28)(28x-7)=0 | | 11P+3=8P+24 | | 60-3x=2x+5 |